Những câu hỏi liên quan
Quốc Duy Trần
Xem chi tiết
Nguyễn Lê Phước Thịnh
26 tháng 5 2022 lúc 0:46

 

undefined

Quốc Duy Trần
Xem chi tiết
Nguyễn Lê Phước Thịnh
26 tháng 5 2022 lúc 0:39

\(A=\dfrac{\dfrac{3}{8}-\dfrac{3}{10}+\dfrac{3}{11}+\dfrac{3}{12}}{\dfrac{-5}{8}+\dfrac{5}{10}-\dfrac{5}{11}-\dfrac{5}{12}}=\dfrac{-3}{5}\)

Vũ Nguyễn Hải Châu
Xem chi tiết

\(M=0,375-0,3+\dfrac{3}{11}+\dfrac{3}{12}-0,625+0,5-\dfrac{5}{11}-\dfrac{5}{12}\)

\(M=\left(0,375-0,625\right)+\left(0,5-0,3\right)+\left(\dfrac{3}{11}-\dfrac{5}{11}\right)+\left(\dfrac{3}{12}-\dfrac{5}{12}\right)\)

\(M=-0,25+0,2-\dfrac{2}{11}-\dfrac{1}{6}\)

\(M=-\dfrac{263}{660}\)

Vân Nguyễn Thị
Xem chi tiết
Nguyễn Hoàng Minh
7 tháng 9 2021 lúc 10:16

\(A=\dfrac{\dfrac{3}{8}-\dfrac{3}{10}+\dfrac{3}{11}+\dfrac{3}{12}}{-\dfrac{5}{8}+\dfrac{5}{10}-\dfrac{5}{11}-\dfrac{5}{12}}+\dfrac{\dfrac{3}{2}+\dfrac{3}{3}-\dfrac{3}{4}}{\dfrac{5}{2}+\dfrac{5}{3}-\dfrac{5}{4}}\\ A=\dfrac{3\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}{-5\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}+\dfrac{3\left(\dfrac{1}{2}+\dfrac{1}{3}-\dfrac{1}{4}\right)}{5\left(\dfrac{1}{2}+\dfrac{1}{3}-\dfrac{1}{4}\right)}\\ A=\dfrac{-3}{5}+\dfrac{3}{5}=0\)

Lấp La Lấp Lánh
7 tháng 9 2021 lúc 10:16

\(A=\dfrac{0,375-0,3+\dfrac{3}{11}+\dfrac{3}{12}}{-0,625+0,5-\dfrac{5}{11}-\dfrac{5}{12}}+\dfrac{1,5+1-0,75}{2,5+\dfrac{5}{3}-1,25}=\dfrac{3\left(0,125-0,1+\dfrac{1}{11}+\dfrac{1}{12}\right)}{-5\left(0,125-0,1+\dfrac{5}{11}+\dfrac{5}{12}\right)}+\dfrac{\dfrac{3}{5}\left(2,5+\dfrac{5}{3}-1,25\right)}{2,5+\dfrac{5}{3}-1,25}=-\dfrac{3}{5}+\dfrac{3}{5}=0\)

quân
Xem chi tiết
Lê Vũ Anh Thư
Xem chi tiết
ST
16 tháng 9 2017 lúc 16:40

\(A=\frac{0,375-0,3+\frac{3}{11}+\frac{1}{4}}{0,625+0,5-\frac{5}{11}-\frac{5}{12}}\)

\(=\frac{\frac{3}{8}-\frac{3}{10}+\frac{3}{11}+\frac{3}{12}}{\frac{5}{8}+\frac{5}{10}-\frac{5}{11}-\frac{5}{12}}\)

\(=\frac{3\left(\frac{1}{8}-\frac{1}{10}+\frac{1}{11}+\frac{1}{12}\right)}{5\left(\frac{1}{8}+\frac{1}{10}-\frac{1}{12}-\frac{1}{12}\right)}\)

\(=\frac{3.263.\frac{1}{1320}}{5.67.\frac{1}{1320}}=\frac{789.\frac{1}{1320}}{335,\frac{1}{1320}}=\frac{789}{335}\)

Dương Nguyễn Ngọc Khánh
Xem chi tiết
Nguyễn Nhật Minh
19 tháng 12 2015 lúc 21:01

\(=\frac{\frac{3}{8}-\frac{3}{10}+\frac{3}{11}+\frac{3}{12}}{\frac{5}{8}-\frac{5}{10}+\frac{5}{11}+\frac{5}{12}}=\frac{3\left(\frac{1}{8}-\frac{1}{10}+\frac{1}{11}+\frac{1}{12}\right)}{5\left(\frac{1}{8}-\frac{1}{10}+\frac{1}{11}+\frac{1}{12}\right)}=\frac{3}{5}\)

võ lê na
Xem chi tiết
Mới vô
7 tháng 1 2018 lúc 8:58

\(A=\dfrac{0,375-0,3+\dfrac{3}{11}+\dfrac{3}{12}}{-0,625+0,5-\dfrac{5}{11}-\dfrac{5}{12}}=\dfrac{-3\left(-0,125+0,1-\dfrac{1}{11}-\dfrac{1}{12}\right)}{5\left(-0,125+0,1-\dfrac{1}{11}-\dfrac{1}{12}\right)}=\dfrac{-3}{5}\)

Cherry Võ
7 tháng 1 2018 lúc 9:01

A=\(\dfrac{0,375-0,3+\dfrac{3}{11}+\dfrac{3}{12}}{-0,625+0,5-\dfrac{5}{11}-\dfrac{5}{12}}\)

A=\(\dfrac{\dfrac{3}{8}-\dfrac{3}{10}+\dfrac{3}{11}+\dfrac{3}{12}}{\dfrac{-5}{8}+\dfrac{5}{10}-\dfrac{5}{11}-\dfrac{5}{12}}\)

A=\(\dfrac{3.\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}{-5.\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}\)

A=\(\dfrac{3}{-5}=\dfrac{-3}{5}\)

Pham Thi Gia Hy
Xem chi tiết
Ngọc Vĩ
13 tháng 7 2016 lúc 22:10

\(\frac{0,375-0,3+\frac{3}{11}+\frac{3}{12}}{-0,625+0,5-\frac{5}{11}-\frac{5}{12}}+\frac{1,5+1-0,75}{2,5+\frac{5}{3}-1,25}\)

\(=\frac{\frac{3}{8}-\frac{3}{10}+\frac{3}{11}+\frac{3}{12}}{-\frac{5}{8}+\frac{5}{10}-\frac{5}{11}-\frac{5}{12}}+\frac{\frac{3}{2}+\frac{3}{3}-\frac{3}{4}}{\frac{5}{2}+\frac{5}{3}-\frac{5}{4}}\)

\(=\frac{3\left(\frac{1}{8}-\frac{1}{10}+\frac{1}{11}+\frac{1}{12}\right)}{\left(-5\right)\left(\frac{1}{8}-\frac{1}{10}+\frac{1}{11}+\frac{1}{12}\right)}+\frac{3\left(\frac{1}{2}+\frac{1}{3}-\frac{1}{4}\right)}{5\left(\frac{1}{2}+\frac{1}{3}-\frac{1}{4}\right)}\)

\(=\frac{-3}{5}+\frac{3}{5}=0\)